The possible significance of trisomy 8 in acute myeloid leukemia - Vaniawala, Salil N.; Patel, Monika V.; Chavda, Pratik D.; Zaveri, Shivangi H.; Gadhia, Pankaj K. (International Journal of Research in Medical Sciences, 2017)
Background: Acute myeloid leukemia (AML) is a heterogeneous disorder that results from a block in the differentiation of haematopoietic progenitor cells along with uncontrolled proliferation. Trisomy 8 is the most common recurring numerical chromosomal aberrations in acute myeloid leukemia (AML). It occurs either as a sole anomaly or together with other additional chromosomal aberrations. The prognostic significance of trisomy 8 in presence of other additional chromosomal abnormality depends on clonal cytogenetic changes. The patients with trisomy 8 had shorter survival with significantly increased risk with other chromosomal abnormality. Methods: Total 139 patients were screened between January 2016 to November 2016 who were suspected of AML cases. Bone marrow cultures were set up using conventional cytogenetic methods. Chromosomal preparation was made and subjected to GTG banding technique. Banded metaphases were analysed and karyotyped for further analysis. Results: Cytogenetic evaluation of karyotyped of 139 suspected AML patients showed 52 with t(8;21)(q22;q22), 36 with t(15;17)(q22;q12), and 11 with inv(16)(p13;q22). The rest 40 cases found with additional chromosomal abnormalities, of which 16 were sole trisomy 8 and 24 cases were found with other chromosomal abnormalities In addition, only one person found with t(8;21) and trisomy 8, while three person having t(15;17) with trisomy 8. Conclusions: AML is considered to be one of the most important cytogenetic prognostic determinants. Recurrent chromosomal translocation with trisomy 8 varying 1.9% for t(8;21) and 8.3% for t(15;17). In the present study trisomy 8 in AML with known favourable anomalies is very small. Therefore, it cannot be taken as a prognostic marker.